(untitled) (Nepal Medical College Journal, 2021)
The use of grey-scale ultrasound morphology to characterize a pelvic mass may also be called ‘pattern recognition’. The grey-scale ultrasound image provides as much information as that obtained by the surgeon or pathologist when they cut a surgical specimen to see what it looks like inside. Aim of our study is to characterize the ovarian mass by ultrasound. The study was conducted in Department of Radiology and Imaging, College of Medical Sciences, Bharatpur. Patients with suspected ovarian mass in Gynecology OPD were included in our study. A prospective cross-sectional study was conducted on 60 patients in college of medical science, Bharatpur, over the period of one year (from November 2019 to October 2020). Present study showed benign ovarian (90.0%) pathology are the most commonly encountered ovarian mass. Ovarian mass is most common in adult female of age 15-30 years and malignant ovarian mass was most common among the age group of 30-60 years. Among benign pathology of ovary simple follicular cysts are most common (39.0%), followed by hemorrhagic cyst (31.0%), dermoid cyst (17.0%), chocolate cyst (9.0%) and ectopic pregnancy (4.0%). Among the malignant ovarian mass serous cystadenocarcinoma and mucinous cystadenocarcinoma showed similar frequency (33.0% each) and followed by immature teratoma and krukenberg tumor (17.0% each). Ultrasound parameters like size, septal thickness, solid component and spectral doppler (RI ans PI) are very helpful for determination of malignant pathology. In this study the sensitivity and specificity of size parameter is least (40.3% and 60.2%) and highest in solid component and spectral Doppler parameter (PI) being (82.0% and 92.0%). Combined study of grey scaleand spectral Doppler study plays crucial role in characterization of ovarian mass to differentiate between benign and malignant pathology.